Inheritance in metal: A record of the sacred arts of the del Valle goldsmiths - Bonilla Soto, Luis Carlos (2019)
Received: 17-06-2019Approved: 15-07-2019 The article classifies the contributions made by the goldsmiths of the Del Valle family to the Costa Rican patrimony, including a description and history of the portable art objects fashioned by them, which are currently stored and protected in various catholic churches.